Credit risk assessment : the new lending system for borrowers, lenders, and investors - Abrahams, Clark R., 1951-; Zhang, Mingyuan, 1960- (Hoboken, N.J. : Wiley, 2009)
Clark and Mingyuan start with an insightful and comprehensive description of how market participants contributed to the current crisis in the residential mortgage markets and the root causes of the crisis. They then proceed to develop a new residential mortgage lending system that can fix our broken markets because it addresses the root causes. The most impressive attributes of their new system is its commonsense return to the basics of traditional underwriting, combined with factors based on expert judgment and statistics and forward-looking attributes.
Unpacking the financial crisis -- The case for a comprehensive credit assessment framework -- The lender and the underwriting gap -- The borrower and loan affordability -- The investor and financial innovation -- Crisis intervention and prevention.
Includes bibliographical references and index.
Print version record.
John Wiley and Sons
Keywords: Credit -- Management; Consumer credit -- Management; Bank loans -- Management; Risk management; Risk Management; x; x; x; Gestion du risque; risk management; BUSINESS & ECONOMICS -- Finance; Bank loans -- Management; Consumer credit -- Management; Credit -- Management; Risk management; Kredietverzekering; Risicobeheersing; Leningen